PENDIDIKAN AGAMA DALAM SISTEM PENDIDIKAN DI INDONESIA (Survey Historis Era Pemerintahan Soekarno) - Edi Susanto (TADRIS: Jurnal Pendidikan Islam, 2009)
The existence of religion education in Indonesia from the beginning has raised polemic circumstance, it appears many policies on the existence of religion education. This article portrayals the religion education in Soekarno’s regime. In his era, in which consistend of three periods; revolutionary era, parliementary democracy, and guide democracy, was early seen how the political policies of the government colored the design and construction of religion education.